miR-126 Mimic Counteracts the Increased Secretion of VEGF-A Induced by High Glucose in ARPE-19 Cells - Roberta Sanguineti; Alessandra Puddu; Massimo Nicolò; Carlo Enrico Traverso; Renzo Cordera; Giorgio L. Viviani; Davide Maggi (Journal of Diabetes Research)
Vascular endothelial growth factor-A (VEGF-A) has a pathologic role in microvascular diabetic complication, such as diabetic retinopathy (DR). miR-126 plays an important role in vascular development and angiogenesis by regulating the expression of VEGF-A. Since levels of miR-126 have been found downregulated in diabetes, this study is aimed at investigating whether hyperglycemia affects expression of miR-126 in a retinal pigment epithelium cell line. ARPE-19 cells were transfected with miR-126 inhibitor or with miR-126 mimic and the respective scramble negative control. After 24 hours, medium was replaced and cells were cultured for 24 hours in normal (CTR) or diabetic condition (HG). Then, we analyzed mRNA levels of miR-126, VEGF-A, PI3KR2, and SPRED1. We also evaluated protein amount of HIF-1α, PI3KR2, and SPRED1 and VEGF-A secretion. The results showed that exposure of ARPE-19 cells to HG significantly decreased miR-126 levels; mRNA levels of VEGF-A and PI3KR2 were inversely correlated with those of miR-126. Overexpression of miR-126 under HG restored HIF-1α expression and VEGF-A secretion to the level of CTR cells. These results indicate that reduced levels of miR-126 may contribute to DR progression by increasing expression of VEGF-A in RPE cells. In addition, we provide evidence that upregulation of miR-126 in RPE cells counteracts the rise of VEGF-A secretion induced by hyperglycemia. In conclusion, our data support a role of miR-126 mimic-approach in counteracting proangiogenic effects of hyperglycemia.